Mainstream Magazines, Middlebrow Fiction, and Leslie Gordon Barnard’s “The Winter Road” - Smith, Michelle (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (University of New Brunswick, Dept. of English, 2012)
From the 1920s to the 1960s, anglophone Canadian magazines such as Chatelaine, Maclean’s, and Canadian Home Journal printed a wealth of middlebrow fiction attuned to contemporary problems. Largely overlooked in Canadian studies, these texts reflect the ways in which class tensions and cultural hierarchies defined and shaped a literary field that would, in turn, construct a normative Canadian identity that was implicitly urban, white, heterosexual, and middle-class. Against a backdrop of interwar Montreal, Leslie Gordon Barnard’s “The Winter Road,” serialized in Canadian Home Journal from 1938-39, represents the anxieties and aspirations of middle-class urban professionals during the late 1930s. Barnard engages with such troubling problems as the social and economic tension produced by the competing ideologies of capitalism and socialism. In the end, his story reflects a fictional world in which the desire for personal fulfilment can be balanced with the demands of the public good, thereby generating an arguably middlebrow stance to a volatile modern society.